Estudo da relação entre os níveis de indicadores biológicos de exposição ao tolueno e o estresse oxidativo em expostos ocupacionalmente a tintas - Moro, Angela Maria (2010)
Paints occupational exposure is an important health problem due to the wide variety of chemicals and xenobiotics present in their constitution. Organic solvents and heavy metals are among the main chemical constituents of paints. In the view of the variety of substances found in paints, can be noted that painters are simultaneously exposed to various xenobiotics, suggesting a case of co-exposure or exposure mixed. Biological monitoring is an essential tool for assessing the risk to health and occupational health practices. Moreover, it is known that there is a close relationship between the xenobiotics constituents of paints and oxidative stress, such as toxicological mechanism. In this study was evaluated oxidative damage by quantification of blood biomarkers of oxidative stress such as malondialdehyde (MDA), reduced glutathione (GSH), δ-aminolevulinate dehydratase enzyme (ALA-D), superoxide dismutase (SOD) and catalase (CAT ), in individuals occupationally exposed to paints (n = 48) and non-exposed subjects (n = 30). Biological monitoring of toluene was performed by quantification of different biomarkers of exposure, urinary hippuric acid and ortho-cresol, and blood toluene. For xylene, styrene, ethylbenzene and lead were quantified urinary levels of methylhippuric acid, mandelic acid, phenylglyoxylic acid and blood lead, respectively. Despite all IBEs were below the biological limit exposure (BEL), significant changes in oxidative stress biomarkers were found in exposed group. Plasma levels of MDA and blood antioxidant enzymes (SOD and CAT) had shown increased in the group of painters when compared with non-exposed group; this increase was accompanied by GSH levels depletion and enzyme ALA-D inhibition. It was also observed several correlations between the oxidative stress biomarkers and biomarkers of exposure to xenobiotics present in paints. By statistical tests were evaluated which of the paints constituents played the greatest influence on changes in oxidative stress biomarkers, in this case of co-exposure. Among the exposure biomarkers tested, blood toluene was suggested as the main responsible for increased lipid peroxidation; in addition, it was appointed as a new and important inhibitor of the enzyme ALA-D. Thus, it is suggested that a joint evaluation of biomarkers of exposure and oxidative stress biomarkers might be useful to ensure, in longterm, the worker s health.